RE-EXAMINATION OF NIGERIA AGRICULTURAL EXPENDITURE: GOVERNANCE PERSPECTIVES : Governance and the agricultural expenditure in Nigeria - Abdullahi Musa Sakanko (International Journal of Economics Development Research (IJEDR), 2020)
The weapon of every growing economy can be associated with governance, as good governance put all action and inaction in one basket and make sure that is channel through transparent, effective, and accountable to provide enabling atmosphere for the economy to strive for the betterment of the citizen. It is on this remark, this study investigates the effect of governance in the agricultural expenditure in Nigeria, Error Correction mechanism was employed on the time-series data collected from National statistics bulletins and the empirical results revealed that accountability and corruption control have a positive and statistically significant effect on the agricultural expenditure in the short run within the sample period. However, the agricultural output was found to have a decline effect on the agricultural expenditure in the short run in Nigeria. This study, therefore, recommended that the government at all levels should ensure that corrupt governance is fought or reduced to a minimum level in order to achieve an effective allocation of funds to the agricultural sector to improve performance and contribution to economic growth and development. Accountability should be adopted in every level of government to reduce waste, encourage competence and consistency, liable, responsible to promote investment, and ethics.